UMPSA leads Festival Idea@Pahang in expanding ecosystem of knowledge and innovation - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 12 October 2025 - The organisation Festival Idea@Pahang 2025 was celebrated with great enthusiasm and innovation through the Commercialisation Day, AI Generation Festival (AiGenFest), Advanced TVET Exhibition, Open Laboratory Day, and I’m Mahasiswa UMPSA Open Day, strengthening the hub of strategic thinking and innovation through the participation of various ministries, government agencies, industries, and higher education institutions, particularly in Pahang.